Structural, Electronic, Vibrational and Pharmacological Investigations of Highly Functionalized Diarylmethane Molecules Using DFT Calculations, Molecular Dynamics and Molecular Docking. (16th March 2023) - Kole, Priyanka B.; Kollur, Shiva Prasad; Revanasiddappa, H. D.; Shivamallu, Chandan; Costa, Renyer A.; Junior, Earle S. A.; Anselmo, Lucas M.; da Silva, Jonathas N.; Srinivasa, Chandrashekar; Syed, Asad; Singh, Fateh V.
Abstract: Present work describes the UV–Visible and FT-IR spectral behavior of highly functionalized diarylmethanes via theoretical investigations. Analyses of both theoretical and experimental UV data were in good agreement with the assigned bands. In addition, calculations pertaining to natural bond orbitals (NBOs) and mapped molecular electrostatic potential surface (MEPS) were also performed, revealing that the strongest hyperconjugative intramolecular interactions involves the π ⟶ π ∗, LP ⟶ σ ∗ and n → π * transitions in the D and A rings. Further, the theoretical vibrational analysis revealed several characteristic vibrations that may be used as a diagnostic tool for other diarylmethanes and also indicated that the experimental bands related to the nitrile group occur in regions lower than usual, which confirms high conjugation of the triple bond with the aromatic system. Molecular dynamics (MD) and molecular docking calculations were performed in order to evaluate the behavior of such molecules in aqueous medium and the pharmacological potential. Another interesting observation in this study is the HOMO–LUMO analysis, which showed that the global reactivity values changed according to the type of substituent groups.